2007
DOI: 10.1021/pr070525r
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Hepatocellular-Carcinoma-Associated Antigens and Autoantibodies by Serological Proteome Analysis Combined with Protein Microarray

Abstract: To comprehensively study autoantibodies in patients with hepatocellular carcinoma (HCC), we used an approach-based serology and proteomics technologies. Total proteins extracted from HepG2 cells and HepG2.2.15 cells were separated by two-dimensional gel electrophoresis (2DE) and then transferred onto polyvinylidene difluoride (PVDF) membranes, which were subsequently incubated with sera from HCC patients or from normal controls. As a result, 13 HCC-associated antigens were identified. Antigenicity of eight pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 45 publications
2
52
0
Order By: Relevance
“…Other proteins that have also been shown to be elevated in hepatocellular carcinoma include fibrinogen gamma chain precursor [30], glutathione S transferase [31], glycerol-3-phosphate dehydrogenase [32], histone-binding protein RBBP4 [33] and nucleophosmin [34]. Lamin-A/C was elevated in sera of patients with a hepatocellular carcinoma [35]. Other proteins have been shown to be associated with different tumor types such as L-lactate dehydrogenase B chain which is elevated in lung cancer [36], niban which is overexpressed in renal tumors [37], and non-syndromic hearing impairment protein 5 which shows altered expression in colorectal cancer [38].…”
Section: Discussionmentioning
confidence: 98%
“…Other proteins that have also been shown to be elevated in hepatocellular carcinoma include fibrinogen gamma chain precursor [30], glutathione S transferase [31], glycerol-3-phosphate dehydrogenase [32], histone-binding protein RBBP4 [33] and nucleophosmin [34]. Lamin-A/C was elevated in sera of patients with a hepatocellular carcinoma [35]. Other proteins have been shown to be associated with different tumor types such as L-lactate dehydrogenase B chain which is elevated in lung cancer [36], niban which is overexpressed in renal tumors [37], and non-syndromic hearing impairment protein 5 which shows altered expression in colorectal cancer [38].…”
Section: Discussionmentioning
confidence: 98%
“…However, tumors > 5 cm in diameter are present more frequently in patients with anti-eEF2 autoantibodies compared with those with small tumors (> 5 cm in diameter) (P < 0.05) [35] . The rates of detection of autoantibodies against AIF and hnRNP A2 in patients with HCC without regional lymph node metastasis were significantly higher compared with those with regional lymph node metastasis (P < 0.05) [35] . There is a significant difference in size of tumors of patients with HCC cases that correlates with prevalence of autoantibodies against hnRNP L-67-88, with the average tumor size of 5.84 ± 4.23 cm in patients with detectable autoantibodies whereas 3.70 ± 2.07 cm in patients without detectable autoantibodies [36] .…”
Section: Association Of the Prevalence Of Autoantibodies With The CLImentioning
confidence: 90%
“…There is evidence, however, showing that there are no statistically significant differences in patients with HCC in the prevalence of autoantibodies against DEAD box 3, eEF2, AIF, hnRNP A2, PBP, and TIM and patients' characteristics of sex, histological grade, or TNM classification [35] . However, tumors > 5 cm in diameter are present more frequently in patients with anti-eEF2 autoantibodies compared with those with small tumors (> 5 cm in diameter) (P < 0.05) [35] . The rates of detection of autoantibodies against AIF and hnRNP A2 in patients with HCC without regional lymph node metastasis were significantly higher compared with those with regional lymph node metastasis (P < 0.05) [35] .…”
Section: Association Of the Prevalence Of Autoantibodies With The CLImentioning
confidence: 97%
“…SERPA and protein microarray studies have found autoantibodies to proteins, including EEF2, heterogeneous nuclear ribonucleoprotein A2 (hnRNP A2), DEAD (Asp-Glu-Ala-Asp) box polypeptide 3, X-linked (DDX3X), apoptosis inducing factor (AIF), prostatic binding protein (PBP), and TIP to be significantly higher in patients with hepatocellular carcinoma than in healthy individuals or patients with chronic hepatitis. The sensitivity of any of the four markers: DDX3X, PBP, EEF2, and AIF was found to be 50% to 85% and increased to 90% when analyzed as a biomarker panel (115).…”
Section: Liver Cancermentioning
confidence: 98%